Negotiating religious moderation in digital narratives: A digital netnography of the Cidahu shelter house conflict on YouTube - Akrima Hilda; Septiana Putri; Dwi Maidatus Salwa; Della Rinjani; Zahra Prasasti Abasiyah; Rosita Fitri Andini; Nawang Wulan; Arditya Prayogi (PT Bina Perfidia Akademia, 2026)
Religious conflicts on social media have increasingly evolved into contests of digital narratives, yet studies mapping the four pillars of religious moderation through a digital netnography approach remain limited. This study aims to analyze the manifestations of national commitment, tolerance, anti-violence, and accommodation to local culture in digital narratives surrounding the Cidahu shelter house conflict in Sukabumi. A qualitative approach employing digital netnography was applied to 228 YouTube comments collected from two news videos published by Kompas TV and analyzed using thematic analysis. The findings reveal that national commitment was primarily reflected in discussions on legality, government authority, and law enforcement, whereas tolerance emerged as the most challenged pillar due to the dominance of hate speech, stereotypes, and polarization (33.3%). Meanwhile, anti-violence and dialogue-oriented narratives appeared less frequently. This study contributes to the literature by providing an empirical mapping of digital narratives based on the four pillars of religious moderation and highlighting the need to reorient Islamic education toward digital literacy and dialogic communication. Abstrak Konflik keagamaan di media sosial terus berkembang menjadi kontestasi narasi digital, namun kajian yang memetakan manifestasi empat pilar moderasi beragama melalui pendekatan digital netnography masih terbatas. Penelitian ini bertujuan menganalisis manifestasi komitmen kebangsaan, toleransi, anti-kekerasan, dan akomodatif terhadap budaya lokal dalam narasi digital mengenai konflik rumah singgah di Cidahu, Sukabumi. Penelitian menggunakan pendekatan kualitatif dengan metode digital netnography terhadap 228 komentar YouTube yang diperoleh dari dua video berita Kompas TV dan dianalisis menggunakan thematic analysis. Hasil penelitian menunjukkan bahwa komitmen kebangsaan termanifestasi melalui narasi legalitas, pemerintah, dan penegakan hukum, sedangkan toleransi menjadi indikator yang paling menghadapi tantangan akibat dominasi hate speech, stereotip, dan polarisasi (33,3%). Sementara itu, narasi anti-kekerasan dan dialog muncul dalam proporsi yang lebih kecil. Penelitian ini berkontribusi memperluas kajian moderasi beragama melalui pemetaan empiris narasi digital berdasarkan empat pilar moderasi beragama serta menegaskan urgensi reorientasi Pendidikan Islam yang mengintegrasikan digital literacy dan dialogic communication.